Lithium Chloride Carbenoids in Bond Activation Reactions - Molitor, Sebastian; Gessner, Viktoria H. (Synlett, 2015)
The field of transition-metal-free bond activation reactions has grown rapidly over the past years. In this context, lithium carbenoids have received renewed interest because of their unique electronic properties and their ambiphilic character. Stabilization of these usually highly reactive and thermally labile compounds has allowed the isolation of species that are stable at room temperature and enabled the development of new applications. In this article, we highlight the latest advances in the stabilization of Li/Cl carbenoids and their use in bond-activation chemistry.1 Introduction2 Classical Carbenoid Chemistry3 Isolation and Properties of Li/Cl Carbenoids4 Reactivity towards Boranes: B–X Bond Activation Reactions5 Reactivity towards Phosphines6 Conclusions
Keywords: carbenoids; lithium; bond activation; dehydrocoupling; carbenes